Returning to the sources: an interview with Saulo de Freitas Araujo about the book series Clássicos da Psicologia (Classics of Psychology) - Araújo, Saulo de Freitas; Fierro, Catriel (Journal of the History of the Behavioral Sciences, 2022)
In this interview with historian of psychology Saulo de Freitas Araujo, we discuss the aims, challenges, and functions of a new book series in which classic psychological works are translated into Portuguese. The interview highlights the importance of the accessibility of primary source documents to psychology education.